2014
DOI: 10.1371/journal.pone.0086517
|View full text |Cite
|
Sign up to set email alerts
|

Human Insulin Does Not Increase Bladder Cancer Risk

Abstract: BackgroundWhether human insulin can induce bladder cancer is rarely studied.MethodsThe reimbursement databases of all Taiwanese diabetic patients from 1996 to 2009 were retrieved from the National Health Insurance. An entry date was set at 1 January 2004 and a total of 785,234 patients with type 2 diabetes were followed up for bladder cancer incidence until the end of 2009. Users of pioglitazone were excluded and the period since the initiation of insulin glargine (marketed after the entry date in Taiwan) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…None of the medications including insulin would affect the risk of lung cancer ( Table 2 ). Our previous studies suggested that insulin use may be associated with some forms of cancer but not all: insulin use is predictive for incidence of [18] but not mortality from [19] non-Hodgkin's lymphoma; it is associated with mortality from but not incidence of bladder cancer [20] , [21] , liver cancer [22] , [23] and pancreatic cancer [24] , [25] ; and it is neither associated with the incidence of nor the mortality from prostate cancer [26] [28] and gastric cancer [29] , [30] . Putting together the findings of a lack of predictive power of insulin use on the mortality from lung cancer in our recent prospective 12-year follow-up study [31] and the lack of an association with the incidence of lung cancer in the present study ( Table 2 ), the lung may also be one of those less sensitive organs.…”
Section: Discussionmentioning
confidence: 99%
“…None of the medications including insulin would affect the risk of lung cancer ( Table 2 ). Our previous studies suggested that insulin use may be associated with some forms of cancer but not all: insulin use is predictive for incidence of [18] but not mortality from [19] non-Hodgkin's lymphoma; it is associated with mortality from but not incidence of bladder cancer [20] , [21] , liver cancer [22] , [23] and pancreatic cancer [24] , [25] ; and it is neither associated with the incidence of nor the mortality from prostate cancer [26] [28] and gastric cancer [29] , [30] . Putting together the findings of a lack of predictive power of insulin use on the mortality from lung cancer in our recent prospective 12-year follow-up study [31] and the lack of an association with the incidence of lung cancer in the present study ( Table 2 ), the lung may also be one of those less sensitive organs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent observational study that used data from the CPS II cohort study showed a higher risk of invasive BCa among insulin users compared with diabetics who did not use insulin . A large Taiwanese population‐based study showed a correlation between human insulin use and BCa only in age‐sex adjusted multivariate models, which became insignificant when results were adjusted for all covariates . The same study also showed that human insulin was predictive of BCa mortality after adjusting for all important confounders, thus including DM duration and smoking habit.…”
Section: Evidence Synthesismentioning
confidence: 93%
“…A number of co‐morbidities and covariates were determined as a status/diagnosis at the time of entry. These have been described in detail previously and included nephropathy, hypertension, chronic obstructive pulmonary disease (a surrogate for smoking), stroke, ischaemic heart disease, peripheral arterial disease, eye disease, obesity, dyslipidemia, urinary tract disease and other cancers. Other medications included statins, fibrate, angiotensin‐converting enzyme inhibitor and/or angiotensin receptor blocker, calcium channel blocker, aspirin, ticlopidine, clopidogrel, dipyridamole and non‐steroidal anti‐inflammatory drugs.…”
Section: Methodsmentioning
confidence: 99%